Block chain technology for digital financial inclusion in the industry 4.0, towards sustainable development? - Mhlanga, David (Frontiers in Blockchain, 2023)
The use of blockchain technology shows a great deal of potential for both the institutionalization of money transfers and the expansion of access to financial services. To ensure that transactions can be verified and recorded using blockchain technology in a distributed ledger, it is believed that regulators and industry professionals have investigated the potential of blockchain technology to streamline and even replace the infrastructure that supports international payments and remittances, such as correspondent banking. This is done to ensure that transactions can be recorded and verified using blockchain technology. The paper set out to examine the impact that blockchain technology has had on bringing previously excluded people into the financial mainstream and to offer commentary on the most valuable lessons and benefits of sustainable development. The study used a systematic literature review to find the many ways in which blockchain technology can aid digital financial inclusion, such as the use of blockchain technology in financial transactions, the use of blockchain technology as a tool for increasing financial savings, the application of blockchain technology to the provision of credit, and the utilization of blockchain technology in the process of providing insurance. This research also found that eight of the Sustainable Development Goals for 2030 include financial inclusion as a target. Thus, the study found that if the technology behind blockchains can be successfully deployed to increase financial inclusion, then sustainable development can be secured on many different fronts. Investments in blockchain must be taken seriously by governments, especially those in emerging nations if financial inclusion is to be expanded.